2023
DOI: 10.1002/cncr.34716
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA‐based molecular residual disease detection for treatment monitoring in advanced melanoma patients

Abstract: Background Immune checkpoint inhibitors (ICIs) have substantially improved overall survival in patients with advanced melanoma; however, the lack of biomarkers to monitor treatment response and relapse remains an important clinical challenge. Thus, a reliable biomarker is needed that can risk‐stratify patients for disease recurrence and predict response to treatment. Methods A retrospective analysis using a personalized, tumor‐informed circulating tumor DNA (ctDNA) assay on prospectively collected plasma sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…An alternative use of ctDNA in the adjuvant setting is to identify those patients who are not responding to adjuvant therapy or to detect molecular relapse following its completion. In the post‐immunotherapy cohort ( n = 10, stage II/IV) Eroglu et al 1 . found that all of the ctDNA negative patients remained disease‐free whereas the three patients with ctDNA detected had disease progression.…”
Section: Trial Name Main Hypothesis Phase Nct Nomentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative use of ctDNA in the adjuvant setting is to identify those patients who are not responding to adjuvant therapy or to detect molecular relapse following its completion. In the post‐immunotherapy cohort ( n = 10, stage II/IV) Eroglu et al 1 . found that all of the ctDNA negative patients remained disease‐free whereas the three patients with ctDNA detected had disease progression.…”
Section: Trial Name Main Hypothesis Phase Nct Nomentioning
confidence: 99%
“…Similarly in colorectal cancer, noninferiority of a ctDNA‐guided approach compared to adjuvant chemotherapy has been demonstrated in stage II disease 8,9 . Eroglu et al 1 . add to this literature by providing further insight into ctDNA dynamics during immune‐checkpoint inhibitors (ICI) in both adjuvant and advanced melanoma.…”
Section: Trial Name Main Hypothesis Phase Nct Nomentioning
confidence: 99%
See 3 more Smart Citations